The Influence Of Transformational Leadership Style On Employee Performance At Bri Jennae Unit, Soppeng Regency - Andi Jenni Indriakati; Nurul Irma Sari; Jesica Ayu Pamula; Asmini Asmini; Puji Rahmah; Wahyulis Hersya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study aims to determine the influence of transformational leadership style on employee performance at the BRI Jennae Unit, Soppeng Regency. This research employs a quantitative approach using a survey method. The population consists of all 13 employees of the BRI Jennae Unit, Soppeng Regency, with a saturated sampling technique applied. Data were collected through questionnaires using a Likert scale and analyzed using simple linear regression with the assistance of SPSS software. The results indicate that transformational leadership style has a positive and significant effect on employee performance, with a significance value of 0.001 (p < 0.05). This means that the better the implementation of transformational leadership style, the higher the employee performance at the BRI Jennae Unit, Soppeng Regency